Implementasi Kurikulum Pendidikan Islam Masa Kini Ditinjau dari Beberapa Teori Filsafat Pendidikan - Fikri, Muhammad Rijalul (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2025)
This research aims to identify the Islamic education curriculum of this era by linking the philosophy of education theory. This research uses a qualitative method with a literature study approach. Data were collected through reviewing various relevant literature sources, including books, journals, articles, and official documents related to the Islamic education curriculum and educational philosophy theory. The author analyzed the data using the synthesis analysis method. Data analysis was conducted by identifying the main themes relevant to the purpose of this research. The result of this research is that the philosophy of education theory in collaboration with the Islamic Education curriculum will not only equip students with academic knowledge, but also with moral values and skills needed to face future challenges.